Pilgrimage As A Form Of Transcendental Communication: A Study At The Burial Site Of Habib Abdurrahman Bin Abdullah Al-habsyi - Achmad Jamil; Rizki Briandana; Ahmad Hannan; Muhammad Raqib Mohd Sofian (Department of Islamic Communication and Broadcasting, 2024)
Volume: 7 No: (Page:209-224)